Assessing Plyometric Ability during Vertical Jumps Performed by Adults and Adolescents - Brandon W. Snyder; Shawn N. Munford; Chris Connaboy; Hugh S. Lamont; Shala E. Davis; Gavin L. Moir (MDPI AG, 2018)
The purpose of this study was to compare different methods for assessing plyometric ability during countermovement (CMJ) and drop jumps (DJ) in a group of adults and adolescents. Ten resistance-trained adult men (age: 22.6 ± 1.6 years) and ten adolescent male basketball players (age: 16.5 ± 0.7 years) performed a CMJ and a DJ from a height of 0.40 m. Jump height (JH), contact time, normalized work (WNORM), and power output (PONORM) during the absorption and propulsion phases were calculated from force platforms and 3-D motion analysis data. Plyometric ability was assessed using the modified reactive strength index (RSIMOD during CMJ) and the reactive strength index (RSI during DJ) as well as three indices using propulsion time, propulsion work (PWI), and propulsion power. Adults jumped significantly higher than adolescents (mean difference [MD]: 0.05 m) while JH (MD: 0.05 m) and ground contact time (MD: 0.29 s) decreased significantly from CMJ to DJ. WNORM (MD: 4.2 J/kg) and PONORM (MD: 24.2 W/kg) during the absorption phase of CMJ were significantly less than these variables during the propulsion phases of the jumps. The reactive strength index variants increased significantly from the CMJ to DJ (MD: 0.23) while all other plyometric indices decreased significantly. Neither RSIMOD nor RSI contributed significantly to the prediction of JH during CMJ and DJ, respectively, while PWI was able to explain ≥68% of the variance in JH. Variants of the reactive strength index do not reflect the changes in mechanical variables during the ground contact phase of CMJ and DJ and may not provide an accurate assessment of plyometric ability during different vertical jumps.